Introcdution to computer science using Java - Liberty, Jesse (Glencoe/McGraw-Hill, 2004)
Glencoe’s Introduction to Computer Science Using Java provides students with a highly visual way of learning Java programming. This colorful text provides the information needed for students enrolled in Computer Science I courses, and for students planning to take the AP Computer Science A exam (which has recently switched from C++ to Java). The textbook immediately introduces students to concepts that are essential to object-oriented programming and develops these concepts throughout various code programs and examples. Programs are examined line-by-line through in-text code blocks. Complete programs are then provided for students to compile and run. The output for every program is also provided either in the book or on the teacher CD so students can see what happens when the code is run.